TEACHER’S SPEECH AS A COMMUNICATIVE TOOL (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In the realm of education, the teacher's speech serves as a pivotal communicative instrument, shaping the dynamics of classroom interaction and influencing students' learning experiences. Beyond the mere transmission of knowledge, the way teachers articulate, modulate, and employ language significantly impacts student engagement, comprehension, and participation.